A Conjugated Schiff-Base Macrocycle Weakens the Transverse Crystal Field of Air-Stable Dysprosium Single-Molecule Magnets - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2022)
Self-condensation of bifunctional 8-aminoquinoline-2-carbaldehyde templated by dysprosium(iii) ions followed by the replacement of axial ligands with triphenylsilanol in the presence of Et3N produced two belt macrocycle complexes, [Dy(L1N6)(Ph3SiO)2][ClO4] (1) and [Dy(L1N6)(Ph3SiO)2][OTf] (2) (L1N6 = 2,5,8-triaza-1(8,2),4,7(2,8)-triquinolinacyclononaphane-2,5,8-triene). For comparison, other kinds of belt macrocycle complexes [Dy(RRRR-L2N6)(Ph3SiO)2][(3-Br-C6H4)B(C6H5)3] (3R), [Dy(SSSS-L2N6)(Ph3SiO)2][(3-Br-C6H4)B(C6H5)3] (3S), [Dy(RRRR-L2N6)(Ph3SiO)2][(4-Br-C6H4)B(C6H5)3] (4R) and [Dy(SSSS-L2N6)(Ph3SiO)2][(4-Br-C6H4)B(C6H5)3] (4S) (L2N6 = (2E,5E,8E,11E)-3,5,9,11-tetraaza-1,7(2,6)-dipyridina-4,10(1,2)-dicyclohexanacyclododecaphane-2,5,8,11-tetraene) were also prepared using the same procedure except that the equatorial macrocycle was built from a [2 + 2]-condensation of cyclohexane-1,2-diamine and pyridine-2,6-dicarbaldehyde. These structurally similar complexes have almost identical axial Dy-O distances but distinguishable equatorial Dy-N distances, i.e. longer Dy-N distances were observed in 1 and 2, suggesting a weaker equatorial crystal field. Magnetism measurements reveal a typical zero-field single-molecule magnet (SMM) behavior with the effective energy barriers (Ueff) up to 1732(43) K, 1680(9) K, 1363(22) K/1415(24) K and 1369(34) K/1434(29) K for 1, 2, 3R/3S and 4R/4S, respectively. The experimental results are supported by ab initio calculations, which exhibit relaxation of the magnetization via higher excited states in 1 and 2 as the consequence of a weaker equatorial crystal field and a less distorted coordination geometry, which efficiently hampers the transverse components of magnetization. This work unequivocally evidenced the dominance of L1N6 over L2N6 in weakening the transverse crystal field, providing a new route to construct high-performance air-stable lanthanide SMMs. © 2022 The Royal Society of Chemistry.